Ion gyro‐harmonic structuring in the stimulated radiation spectrum and optical emissions during electron gyro‐harmonic heating. Issue 3 (25th March 2013) - Mahmoudian, A.; Scales, W. A.; Bernhardt, P. A.; Samimi, A.; Kendall, E.; Ruohoniemi, J. M.; Isham, B.; Vega‐Cancel, O.; Bordikar, M.
<x xml:space="preserve">Abstract</x> [1] Stimulated electromagnetic emissions (SEEs) are secondary radiation produced during active space experiments in which the ionosphere is actively heated with high power high frequency (HF) ground‐based radio transmitters. Recently, there has been significant interest in ion gyro‐harmonic structuring the SEE spectrum due to the potential for new diagnostic information available such as electron acceleration and creation of artificial ionization layers. These relatively recently discovered gyro‐harmonic spectral features have almost exclusively been studied when the transmitting frequency is near the second electron gyro‐harmonic frequency. The first extensive systematic experimental investigations of the possibility of these spectral features for third electron gyro‐harmonic heating are provided here. Discrete spectral features shifted from the transmit frequency ordered by harmonics of the ion gyro‐frequency were observed for third electron gyro‐harmonic heating for the first time at a recent campaign at the High Frequency Active Auroral Research Program (HAARP) facility. These features were also closely correlated with a broader band feature at a larger frequency shift from the transmit frequency known as the downshifted peak (DP). The power threshold of these spectral features was measured, as well as their behavior with heater beam angle, and proximity of the transmit frequency to the third electron gyro‐harmonic frequency. Comparisons were also made with similar spectral features observed during second electron gyro‐harmonic heating during the same campaign. A theoretical model is provided that interprets these spectral features as resulting from parametric decay instabilities in which the pump field ultimately decays into high frequency upper hybrid/electron Bernstein and low frequency neutralized ion Bernstein IB and/or obliquely propagating ion acoustic waves at the upper hybrid interaction altitude. Coordinated optical and SEE observations were carried out in order to provide a better understanding of electron acceleration and precipitation processes. Optical emissions were observed associated with SEE gyro‐harmonic features for pump heating near the second electron gyro‐harmonic during the campaign. The observations affirm strong correlation between the gyro‐structures and the pump‐induced optical emissions.